Effects of olive oil-treated diet and key lime juice-treated drinking water on intake and growth performance of quail - Mohammad Mijanur Rahman; Suhaily Auni Sukor; Nafiatul Umami; Suniza Anis Mohamad Sukri (ResearchGate, 2025)
The study aims to determine the efficacy of an olive oil-treated diet and key lime juice (KLJ)-treated drinking water on the intake and growth performance of quail. A total of 324 quails were divided into 6 groups: commercial feed (I) as a control group and formulated feed (II-VI) as a treatment group. Formulated feeds were prepared using olive oil, and drinking water was treated with KLJ at 0ml/kg+0ml/L (II), 1.5ml/kg+2.0ml/L (III), 3.0ml/kg+2.0ml/L (IV), 1.5ml/kg+4.0ml/L (V), and 3.0ml/kg+4.0ml/L (VI), respectively. Each group included 54 quails with 6 replicates of 9 birds each. The formulated feed contained lower crude protein (CP), ether extract (EE), crude ash (CA), and metabolizable energy (ME), but higher crude fiber (CF) than commercial feed. The treatment groups had no (P>0.05) effect on dry matter, organic matter, or CP intakes. However, there was a higher EE intake in the control group, while a higher CF intake was observed in the treatment group. The control group showed lower water intake than others. Groups IV and V showed higher weight gain than groups II, III, and VI, but no difference was observed in group I. Regarding feed conversion ratio (FCR), groups IV and V showed the lowest and similar values, while group II demonstrated the highest. Considering its positive effects on weight gain and FCR, it can be recommended to add olive oil to the diet and KLJ in water.